In silico analyses of penicillin binding proteins in Burkholderia pseudomallei uncovers SNPs with utility for phylogeography, species differentiation, and sequence typing. - Heather P McLaughlin; Christopher A Gulvik; David Sue (Public Library of Science (PLoS), 2022)
Burkholderia pseudomallei causes melioidosis. Sequence typing this pathogen can reveal geographical origin and uncover epidemiological associations. Here, we describe B. pseudomallei genes encoding putative penicillin binding proteins (PBPs) and investigate their utility for determining phylogeography and differentiating closely related species. We performed in silico analysis to characterize 10 PBP homologs in B. pseudomallei 1026b. As PBP active site mutations can confer β-lactam resistance in Gram-negative bacteria, PBP sequences in two resistant B. pseudomallei strains were examined for similar alterations. Sequence alignments revealed single amino acid polymorphisms (SAAPs) unique to the multidrug resistant strain Bp1651 in the transpeptidase domains of two PBPs, but not directly within the active sites. Using BLASTn analyses of complete assembled genomes in the NCBI database, we determined genes encoding PBPs were conserved among B. pseudomallei (n = 101) and Burkholderia mallei (n = 26) strains. Within these genes, single nucleotide polymorphisms (SNPs) useful for predicting geographic origin of B. pseudomallei were uncovered. SNPs unique to B. mallei were also identified. Based on 11 SNPs identified in two genes encoding predicted PBP-3s, a dual-locus sequence typing (DLST) scheme was developed. The robustness of this typing scheme was assessed using 1,523 RefSeq genomes from B. pseudomallei (n = 1,442) and B. mallei (n = 81) strains, resulting in 32 sequence types (STs). Compared to multi-locus sequence typing (MLST), the DLST scheme demonstrated less resolution to support the continental separation of Australian B. pseudomallei strains. However, several STs were unique to strains originating from a specific country or region. The phylogeography of Western Hemisphere B. pseudomallei strains was more highly resolved by DLST compared to internal transcribed spacer (ITS) typing, and all B. mallei strains formed a single ST. Conserved genes encoding PBPs in B. pseudomallei are useful for strain typing, can enhance predictions of geographic origin, and differentiate strains of closely related Burkholderia species.